INDEKS ALBUMEN, INDEKS YOLK, DAN HAUGH UNIT TELUR ITIK ALABIO YANG DIRENDAM DENGAN DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Teti Heryani; Muhammad Riyadhi; Abrani Sulaiman (www.ulm.ac.id, 2024)
This study aims to determine the length of the shelf life of Alabio duck eggs after soakingwuluh starfruit leaves (Averrhoa bilimbi L.). and determine the effect of soaking Alabio duckeggs using wuluh starfruit leaves on the quality of Alabio duck eggs. This research methoduses a completely randomized design (CRD) with 4 treatments and 5 replicates, eachreplicate consisting of 12 Alabio duck eggs. The treatments in this study were P0 = control orwithout soaking, P1 = soaking eggs for 12 hours using 50% star fruit leaf powder solution, P2= soaking eggs for 18 hours using 50% star fruit leaf powder solution, P3 = soaking eggs for12 hours using 505% star fruit leaf powder solution. After soaking, the eggs were allowed tostand at room temperature and measurements were taken on days 0, 7, 14, and 21 of storage.Data were analyzed with Anova and DMRT. The results showed that soaking Alabio duckeggs using a solution of star fruit leaf powder with a concentration of 50% had an effect onthe quality of Albumen Index, Egg Yolk Index and Haugh Unit (HU) values. Soaking Alabioduck eggs using wuluh star fruit leaf powder solution can maintain the internal quality valueof Alabio duck eggs and soaking for 24 hours is best.